Rasch Analysis of the Premature Ejaculation Diagnostic Tool (PEDT) and the International Index of Erectile Function (IIEF) in an Iranian Sample of Prostate Cancer Patients - Lin, Chung-Ying (PLoS One, 2016)
BACKGROUND: Male sexual dysfunction is an increasing problem across a variety of general and clinical populations, such as cancer populations; especially among prostate cancer patients who tend to receive treatments that often result in erectile dysfunction (ED) and/or premature ejaculation (PE). Therefore, in order to diagnose ED and PE in these populations, adequate and efficient instruments such as the International Index of Erectile Function 5-item version (IIEF-5) and the Premature Ejaculation Diagnostic Tool (PEDT) are needed. However, since this is an important topic additional evidence of psychometric properties of the IIEF-5 and the PEDT in such samples are required. Thus the aim of the present study was to use Rasch models to investigate the construct validity, local dependency, score order, and differential item functioning (DIF) of both questionnaires in a sample of prostate cancer patients. METHODS: Prostate cancer patients (n = 1058, mean±SD age = 64.07±6.84 years) who visited urology clinics were invited to fill out the IIEF-5 and the PEDT. Construct validity was examined using infit and outfit mean square (MnSq) and local dependency using correlations between each two residual Rasch scores. Score order was investigated using step and average measures of difficulty and DIF using DIF contrast. RESULTS: All IIEF-5 and PEDT items had acceptable infit and outfit MnSq. Step measures revealed that all but two items had disordered categories in terms of scores 1 to 3. Only one local dependency was found, and no items displayed DIF across age, educational level, and help seeking. CONCLUSIONS: The results showed that both the IIEF-5 and the PEDT had sound psychometric properties in the Rasch analyses, although some score disordering could be detected in both instruments. The results of no DIF items in both instruments suggest using them to compare ED and PE across age and educational level is adequate.